2015
DOI: 10.1097/qad.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered HIV-1 gag-specific T-cell responses contribute to slow progression in HLA-A*30-B*13-C*06-positive patients

Abstract: Objective:The HLA-A∗30-B∗13-C∗06 haplotype is reported to be associated with slow disease progression in the HIV-1-infected Northern Han Chinese population, but the mechanism remains unknown.Design:Gag-specific T-cell responses and gag sequencing were performed in nine B′ clade HIV-1-infected HLA-A∗30-B∗13-C∗06-positive slow progressors to understand HLA-associated viral control.Methods:Interferon-γ ELISPOT assays were performed to determine the Gag-specific T-cell responses and cross-reactivity to variant pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…et al . showed that HLA‐A ∗ 30‐B ∗ 13‐C ∗ 06 contributes to the slow progression of HIV infection in the northern Chinese (Zhang et al, ). Three associated alleles, HLA‐C*08:01, C*08:04 and B*13:01 showed different frequencies in Yunnan Han population: HLA‐B*46:01, B*40:01 and B*13:01 were the most predominant alleles at HLA‐B locus; however, HLA‐C*08:01 and C*08:04 were only with frequencies about 4% (Shen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…et al . showed that HLA‐A ∗ 30‐B ∗ 13‐C ∗ 06 contributes to the slow progression of HIV infection in the northern Chinese (Zhang et al, ). Three associated alleles, HLA‐C*08:01, C*08:04 and B*13:01 showed different frequencies in Yunnan Han population: HLA‐B*46:01, B*40:01 and B*13:01 were the most predominant alleles at HLA‐B locus; however, HLA‐C*08:01 and C*08:04 were only with frequencies about 4% (Shen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuleated cells (PBMCs) were isolated from the blood with Lymphoprep (STEMCELL Technologies , origin ). Interferon-γ (IFN-γ) ELISPOT assay was used to measure HPV E1-specific T cell responses in the freshly isolated PBMCs as mentioned previously [ 16 , 20 ]. Briefly, PBMCs were stimulated with overlapping peptide pool (Sigma-Aldrich, USA) representing the whole E1 protein in PVDF plates (Millipore, Bedford, MA, USA) pre-coated with 1-DIK monoclonal antibodies (Machete, Stockholm, Sweden) at 2 × 10 5 PBMCs/well.…”
Section: Methodsmentioning
confidence: 99%
“…IFN-γ enzyme-linked immunospot (ELISPOT) assays were performed as previously described [ 36 ]. In brief, PBMCs were plated in 96-well plates that were precoated with anti-IFN-γ monoclonal antibody at 100,000 cells per well with peptides at a final concentration of 5 μg/ml for pooled peptides, single peptides, and optimal epitopes (BD TM ELISPOT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Viral RNA was extracted from plasma samples obtained from MSM subjects with the QIAamp Viral RNA Mini-kit (Qiagen, UK). The Gag gene was amplified using the SuperScript Polymerase One-Step RT-PCR System (Takara, Dalian, China), followed by a second round of PCR with Gag-specific primers [ 36 ]. PCR products were gel purified with the QIAquick gel extraction kit (Qiagen, UK) and cloned with a TOPO TA cloning kit (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%